THE DEVELOPMENT OF LITERACY LEARNING MEDIA OF ILLUSTRATED STORY BASED ON ANDROID E-BOOK TOWARD READING INTEREST OF THIRD GRADE STUDENTS - Ahmad Syukri Endiawan; Irfai Fathurohman; Santoso (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to develop literacy of illustrated story based on android e-book and find out the improvement of students’ reading interest on the theme of love plant and animals, sub-one the benefits of plants on human life, especially in the third grade of elementary school Terangmas Undaan Kudus. The final product was in form of learning media. The resarch method used was media development with a qualitative approach, Quasi Experimental Design and Nonequivalent Control Group design. This research was conducted at Terangmas Elementary School as the experimental class and Medini elementary school as the control class. The findings showed that the sig. Levene's Test for Equality of Variances of 0.206 because the significance was more than 0.05 or can be served 0.206 < 0.05. Then it can be concluded that data varians between experimental groups and control groups were equally homogeneous. Then based on the table above, it also was known that value sig.(2 tailed) t-test for Equality of Means of 0.000 < 0.005. The results concluded that H0 was rejected and Ha was received. Therefore, there were significant differences between the average reading interests of experimental class and control class.